Meditation and yoga in psychotherapy : techniques for clinical practice - Simpkins, Annellen M. (Wiley Online Library., 2011)
"Consistent with the positive psychology movement, meditative yoga practice puts people on a positive path to actualize change. This timely and unique book provides practical tools for integrating meditation techniques from yoga into traditional treatment plans. Its in-depth coverage not only teaches therapists what to do, but also how, when, and why to use particular techniques. A variety of presenting problems are addressed, including stress management, addictions, anxiety disorders, and attention and learning problems. Clinicians are equipped with step-by-step guidance in the therapeutic use of yoga practices to improve their clients' mental health"--